The acute toxicity of isolates from n-hexane and ethanolic fraction of Dendrophthoe pentandra (L.) Miq. which have immunostimulatory activity - Katrin .; Andreanus A. Soemardji; Asep Gana Soeganda; Iwang Soediro (Indonesian Journal of Pharmacy, 2005)
The acute toxiciy of two isolates from n-hexane fraction and ethanolic fractions of Dendrophthoe pentandra ( L) Miq. leaves have been investigated. Isolate HD54 (ß-sitosterol) Isolat HD54 (ß-sitosterol) isolated from nhexane fraction and ED44 (quercitrine) from ethanolic fraction, which these two fraction have immunostimulatory activity. The acute toxicity test of isolates were investigated on mice after giving a single dose of samples by observing their influences on behavioral responses (pharmacological profile), the development of body weight and mortality each day for 14 days. The observation vital organ have been done on fifteeth day. The results of acute toxicity test after giving the two isolates to males and females mice showed that until a dose of 2000 mg/kg body weight was no animal died and significant toxic effect. Therefore LD50 of the two isolates on mice were higher than 2000 mg/kg body weight. Key words : acute toxicity, immunostimulant, Dendrophthoe pentandra (L.) Miq., LD50 .